112 Global and temporal trends in mortality from ischaemic heart disease: statistics from the World Health Organisation. (May 2019) - Nowbar, Alexandra; Gitto, Mauro; Howard, James; Francis, Darrel; Al-Lamee, Rasha
Abstract : Background: Ischaemic heart disease (IHD) has been considered the top cause of mortality globally. However, countries differ in their rates and there have been changes over time. Methods: We analysed mortality data submitted to the World Health Organization (WHO) from 2005 to 2015 by individual countries. We explored patterns in relationships with age, sex and income, and calculated age-standardised mortality rates for each country in addition to crude death rates. Results: Russia, United States and Ukraine had the largest absolute numbers of deaths among the countries that provided data. Mortality from IHD has progressively decreased from 2005 to 2015 (Figure 1 ). Age-standardised IHD mortality rates per 100, 000 people per year were much higher in Ukraine (324) and Kazakhstan (97) than in Brazil (54) and the UK (46), with much less difference in other causes of death (Figure 2 ). All 4 countries showed a progressive decline in IHD mortality. Conclusions: IHD remains the single largest cause of death in countries of all income groups. Rates are very different between countries and are falling in most countries, indicating great potential for further gains. The political and economic transitions that have taken place in Eastern Europe and Central Asia may have contributed to trends in IHD mortality and risk factor control. Conflict of Interest: nil